Mechanisms for Surveying Storm Disaster Victims to Accelerate Relief for the Victims: A Case Study of Ubolratana District, Khon Kaen Province - Sompanya, Pharinya; Pienkhuntod, Ajirapa (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
This research studied the process of surveying disaster victims to facilitate rapid relief for disaster-stricken individuals. The case study focused on Ubolratana District, Khon Kaen Province, with the objective of examining factors influencing the effectiveness of disaster management. Additionally, the study investigated the problems and obstacles in the disaster management of local administrative organizations (LAO) in the Ubolratana District. The qualitative research approach was employed. Data collection utilized in-depth interviews with a semi-structured questionnaire and participatory observation approach. The qualitative data were processed using content analysis. The key findings of the research are as follows. Disaster management in the areas governed by the 7 LAO in Ubolratana District, Khon Kaen Province, involves several factors contributing to disaster relief. These factors include: 1) The service system of the LAO, comprising prompt surveying, rapid relief for disaster victims, direct and impartial actions, and equitable practices; 2) Personnel of the LAO; 3) Coordination with community leaders and external personnel; and 4) Communication between disaster-affected individuals and the LAO. The research findings can be used as guidelines for surveying disaster-affected individuals to enhance the efficiency of LAO management. Additionally, the results can be utilized to adapt and improve disaster warning systems, and increasing the effectiveness of seeking assistance from the LAO. Moreover, the findings serve as a framework for providing services to disaster-affected individuals in other areas.